Features of municipal services digitalization in Iraq - Svetlana V. Panikarova; Saif S. M. AL-zuwaini (Наука Красноярья)
Background. The digitalization of municipal services represents a critically important direction for modernizing public administration in developing countries. For Iraq, which is experiencing a period of recovery after decades of instability, the implementation of digital technologies in the sphere of municipal services is a key factor in improving the efficiency of public administration, combating corruption, and enhancing the quality of citizen services. Existing research does not contain a comprehensive analysis of municipal service digitalization in the specific conditions of Iraq, which determines the relevance of this study. The aim of the work is to comprehensively analyze the current state of municipal service digitalization in Iraq, identify main obstacles, and develop practical recommendations for improving the efficiency of digital transformation in the municipal sector. To achieve this goal, the following tasks were addressed: examining the organizational foundations of municipal service provision in Iraq; studying the stages of municipal service digitalization; assessing the current state of digital infrastructure; identifying features and barriers to digitalization; developing directions for improving the efficiency of municipal service digitalization.